Predatory drill holes in the oldest thyasirid bivalve, from the Lower Jurassic of South Germany - Karapunar, Baran; Werner, Winfried; Fürsich, Franz; Nützel, Alexander (Lethaia, 2020)
Drill holes provide valuable information about palaeoecological interactions in fossil ecosystems, but the Jurassic drill-hole record is scarce. We report circular drill holes in the infaunal bivalve Eothyasira antiqua(Münster in Goldfuss) from the Pliensbachian grey shales of the Amaltheenton Formation of Franconia, southern Germany. The outcrop of the Amaltheenton Formation at Buttenheim yields a rich bivalve fauna (57 species), which represents a typical soft-bottom community. Eothyasira antiqua, the yet oldest known member of the family Thyasiridae, represents only 1% of the total bivalve specimens from Buttenheim, but shows an exceptionally high frequency of drill holes. With a drilling rate of 81% of the well-preserved articulated specimens, this occurence is unique compared with other drilled bivalve records from the Mesozoic and even from Recent assemblages. The drill holes resemble those of modern naticids with a larger outer opening and are assigned to the ichnospecies Oichnus paraboloides Bromley. Statistical methods show a non-random distribution of the drill holes over the shell surface with a concentration on the central flank. The drill-hole producer was highly efficient in drilling and exhibited a remarkable prey and site-selective behaviour. The drill holes on the moderately deep infaunal Eothyasira suggest that the predator was also infaunal for at least parts of its life and could cope with poorly oxygenated substrate conditions occurring temporarily in the Amaltheenton environment. Drill-hole characteristics point to a gastropod as producer. None of the about 50 gastropod taxa of the Amaltheenton Formation can be associated with the drill holes with certainty, but Hayamia reticulata (Münster) seems to be the most likely candidate. The results of this study support the opinion that drill holes are generally a scarce phenomenon in the Early Jurassic generated by rare, probably highly specialised predators. Preservational biases are considered to have been less important.
CRIS-Team Scopus Importer:2020-09-18
Keywords: drill hole; Early Jurassic; infaunal bivalve; Pliensbachian; predation; Thyasiridae